PENGAMATAN AKTIVITAS TIKUS WISTAR JANTAN DENGAN ALAT OPTO- VARIMEX® PADA KONDISI DIET TINGGI MINYAK TRANS - MASYITA, NURUL; SANTOSO, KOEKOEH; KUSUMORINI, NASTITI; SATYANINGTIJAS, ARYANI SISMIN; SUPIYANI, ATIN (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Excessive energi consumption of high-fat diet increase the body’s adipose tissue which also affect the increased secretion of leptin, this is because leptin secretion is proportional to the mass of adipose tissue. Leptin activates the lateral hypothalamus as the center of hunger and feeding activity. The aim of this study was to obtain the relationship between high trans fat feeding on male Wistar rats and feeding activity. This method uses male Wistar rats (Rattus norvegicus) as an animal model. Sixteen rats were grouped into 4 treatment groups. The first group was given additional feed 20% trans fat, the second group was given additional feed 40% trans fat, a third group was given additional feed 60% trans fat, and the last as a control group. This feed was given once a day for 70 days. Observation of activities perform using Opto-varimex® auto-track system ver. 4.31. The results showed an corellation between activity based doses of trans fat. Keywords: Opto-varimex®, Trans fat, Activity, Wistar rat.